Quatérnios e rotações no espaço - Butzge, Marta Schaeffer (2021)
This work aims to present the set of quaternary numbers and their main properties, using the properties and definitions in the context of analytic geometry as justification. In view of this knowledge associated with the theories contained in vector algebra about linear operators, it also aims to demonstrate the most common forms of parameterization of rotations in space, assuming that they follow the ideas defined for plane rotations, except for small details , thus presenting the three most common types of parameterizations for rotations in space: axis-angle, Euler angles and finally the rotations with unitary quaternary numbers. Considering the number of mathematical operations performed in both parameterizations and conversions between parameterizations, it will be determined which of the rotations offers the lowest computational cost, as well as the characteristics of each rotation.